Seismic behavior of composite shear walls incorporating concrete-filled steel and FRP tubes as boundary elements. (1st August 2018) - Ren, Fengming; Chen, Jinwen; Chen, Guangming; Guo, Yaxin; Jiang, Tao
Highlights: Pilot study on a new composite shear wall with FRP tube in boundary elements. Load and deformation capacities of the new wall are higher than normal shear RC wall. Seismic performance of the new wall is superior to shear wall with CFST columns. Abstract: A new form of a composite shear wall consisting of a reinforced concrete (RC) wall web and two boundary columns, in the form of square concrete-filled steel tubes (CFST) incorporating a carbon fiber–reinforced polymer (CFRP)–confined concrete core, is proposed in this study. To evaluate its seismic performance, the proposed shear wall was tested under constant axial compression force and lateral cyclic loading. Three additional shear walls with different boundary column configurations were also tested: (i) an ordinary shear wall, (ii) a shear wall with CFST boundary columns, and (iii) a shear wall with double-skin CFST boundary columns. The failure mode, load-bearing capacity, ductility, energy dissipation capacity, stiffness degradation, strength degradation, and deformation mode of the four shear walls were thoroughly examined and compared. The results show that the deformation of the proposed shear wall was dominated by bending and that the distribution of axial strain generally satisfied the plane section assumption. The results also show that the seismic performance of the proposed shear wall was superior to that of the ordinary shear wall and the shear wall with CFST boundary columns. The proposed shear wall had the similar load-bearing capacity as the shear wall with double-skin CFST columns, but it had better ductility and larger dissipation capacity. This pilot study demonstrates that the composite shear wall has good potential for improving the performance of buildings constructed in seismic regions.